Biomechanical modeling of spinal ligaments: finite element analysis of L4-L5 spinal segment. Issue 16 (6th December 2021) - Hamidrad, Shabnam; Abdollahi, Masoud; Badali, Vahid; Nikkhoo, Mohammad; Naserkhaki, Sadegh
Abstract: The complex mechanical structure of spine is usually simplified in finite element (FE) modes. In this study, different 3D models of L4-L5 spinal segment distinguished by their ligament modelling were developed (1D truss, 2D shell and 3D space truss elements). All models could be considered validated with respect to range of motion and intradiscal pressure, although their ligament stresses/forces were substantially different. The models with 2D shell and 3D space truss ligaments showed the stress distribution and identified the potential failure/injury locations in ligaments. The model with 3D space truss ligaments showed the stress/force direction (representing collagen fiber directions).